Legality of Islamic Law Against the use of Public Roads for A Wedding Party - Busyro Busyro; Adlan Sanur Tarihoran (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
The public road is a facility for those who passed by the public to support mobility. Islamic teachings determine that the public road is right to base humans who don't can in the sky by anyone. However,some people has utilise the public road for interest marriage party and events personal other so that disturb and hinder activity society. This paper aims to study the legality of Islamic law in middle take effect law positive in Indonesia regarding with use of public roads for doingmarriage reception (walimah) with a focus on two questions: First, what difference among legalization of Islamic law with law positive in case usage the public road for interest carry out party marriage? Second, is regulation of government about settings use the public road for interest party marriage in accordance with the legalization of Islamic law? Type this study is a research library with an approach qualitative. Data collection is carried out with read news, books, and related articles with problem study and analysis with the deductive method. Results of this study show that Islamic law has considered legal when already ijtihad by scholars, different with law positive that the legislation must be validated by the government, and government regulation that regulates using the public road for interest party marriage has produced benefits in accordance with the desired goal achieved in legalization Islamic law.